2020
DOI: 10.1186/s12884-020-03412-x
|View full text |Cite
|
Sign up to set email alerts
|

Community-based bilingual doulas for migrant women in labour and birth – findings from a Swedish register-based cohort study

Abstract: Background Community-based bilingual doula (CBD) services have been established to respond to migrant women’s needs and reduce barriers to high quality maternity care. The aim of this study was to compare birth outcomes for migrant women who received CBD support in labour with birth outcomes for (1) migrant women who experienced usual care without CBD support, and (2) Swedish-born women giving birth during the same time period and at the same hospitals. Methods Register study based on data retrieved from a lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…The aim of this systematic review was to identify options for improving the low birthweight, and prematurity birth outcomes of Indigenous and CALD infants using the social-ecological model to classify intervention types. Overall, the results identified a limited number of interventions that targeted reducing preterm birth and low birthweight in infants of Indigenous and CALD women, though over half (seven of nine) produced statistically significant improvements in these outcomes [ 15 , 16 , 25 29 ]. The greatest improvements in outcomes were seen in interventions that targeted the organisational level of the social-ecological model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The aim of this systematic review was to identify options for improving the low birthweight, and prematurity birth outcomes of Indigenous and CALD infants using the social-ecological model to classify intervention types. Overall, the results identified a limited number of interventions that targeted reducing preterm birth and low birthweight in infants of Indigenous and CALD women, though over half (seven of nine) produced statistically significant improvements in these outcomes [ 15 , 16 , 25 29 ]. The greatest improvements in outcomes were seen in interventions that targeted the organisational level of the social-ecological model.…”
Section: Discussionmentioning
confidence: 99%
“…The interventions that were identified in this review that did provide evidence for improving outcomes took the form of an Aboriginal Maternity Group Practice Program (including Aboriginal grandmothers, Aboriginal Health officers and midwives) (Bertilone, 2015), the use of bilingual doulas [ 25 ], a multidisciplinary service alongside culturally appropriate midwifery care for Aboriginal and Torres Strait Islander mothers and infants [ 29 ], a home visiting program [ 26 ], an Aboriginal Community Controlled Health Organisation “Birthing in Our Community”, which also involved continuity of midwifery carer [ 23 ], a mobile medical van (MOMmobile) that provides on-site care before, during and after pregnancy to CALD women in Miami-Date Country in the United States [ 24 ], and expansion of universal healthcare policies [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another idea proposed by the midwives to facilitate communication during labor, was to cooperate with community-based bilingual doulas (CBDs) who accompany and support women in labor. Support in labor, both physical and emotional, from a doula has been associated with positive experiences of care and for migrant women, improved communication and information-sharing [30][31][32] . Interviews with women and doulas have also revealed that doulas can have a positive impact on maternal emotional wellbeing, by reducing anxiety, sadness and stress, and increasing self-esteem and self-efficacy 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that language barriers are associated with a higher risk of caesarean section [ 29 , 30 ]. We did not have information on language proficiency.…”
Section: Discussionmentioning
confidence: 99%